Nurses' Lived Experiences of Caring for Patients with COVID-19 in Nigeria. (August 2022) - Popoola, Tosin; Popoola, Victor; Nelson, Katherine
Introduction: Since the beginning of the COVID-19 pandemic, nurses have been on the frontline providing care for patients with COVID-19. Caring for patients with COVID-19 can be a rewarding experience for nurses, but research also suggests that nurses experience numerous challenges on the frontline. Objectives: This study aims to explore the experiences of frontline nurses caring for patients with COVID-19 in Nigeria Methods: Ten nurse volunteers working in a COVID-19 isolation center were purposively recruited. Data were collected with a semi-structured interview guide, and a template analysis approach was used to analyze the transcribed interviews. Results: The participants volunteered at the isolation center for safety reasons, professional gain, and concern for humanity. Working at the isolation center was accompanied by changes in working hours, work dynamics, care context and care tools. These changes resulted in personal, professional, and work-related challenges for nurses. However, team spirit, positive patient outcomes, gratitude and family support helped the nurses cope with the challenges. Conclusions: This research highlighted that working on the frontline of COVID-19 is associated with multiple and complex challenges that can impact nurses' personal and professional life. Thus, a tailored approach to support is needed to address the challenges faced by frontline nurses.